Effect of Aeration and KNO3 in Seed Priming on The Germination of Tomato (Solanum lycopersicum) Seeds - Putri Santika; Ilham Muhklisin; Sandile Donald Makama (Agroteknika, 2022)
Seed priming by soaking in KNO3 has been used to enhance seed performance and crop establishment in tomatoes. However, seeds that are immersed in a solution for a long time may be deprived of oxygen during critical phases of imbibition. Aeration during priming is a solution to solve this problem. Thus, this study aims to determine the effect of aeration and KNO3 in seed priming on the germination of tomato seeds. The seeds used in this study were tomato seeds var. Palupi. This study used seven treatments i.e. non-primed, KNO3 moistened paper, KNO3 soaking, KNO3 aeration, water moistened paper, water soaking, and water aeration. The study was arranged in a completely randomized design (CRD). All data were statistically analyzed using one-way ANOVA and followed by means analysis using Fisher’s LSD (Least Significant Difference) test at P<0.05. The result showed that all priming treatments gave a better performance in FGP (Final Germination Percentage), MGT (Mean Germination Time), and GRI (Germination Rate Index) compared to the non-primed. The best treatments, however, were observed in the aeration method in either KNO3 or water in all parameters observed. KNO3 gave a slightly better performance than water in all parameters, although there was no statistical difference between the two treatments.